Assessing the assessments: evidencing and benchmarking student learning outcomes in chemistry : final report. - Schmid, Siegbert; O'Brien, Glennys; Pyke, Simon; Priest, Samuel; Schultz, Madeleine; Southam, Daniel; Bridgeman, Adam; Lawrie, Gwen; Bedford, Simon; Lim, Kieran; Jamie, Ian (Office for Learning and Teaching, 2018)
Final report from a project that developed a tool that enables academic staff to evaluate the fitness for purpose of their assessment tasks. This was important because measurement of the capacity of a task to allow students to prove their achievement of threshold learning outcomes is critical within the new Australian tertiary education regulatory framework. The process of building this tool involved many stages of testing against sets of assessment tasks, individual and group reflection and discussions, refinement of the tool to combat observed problems with its application, further testing with other assessment tasks and further refinement. The final tool is sophisticated and can be applied to evaluate any assessment task against any desired learning outcome. During the process, the project team experienced a transformation in understanding of how assessment can and should operate, and this is an important outcome of the project.